2004
DOI: 10.1002/cne.20222
|View full text |Cite
|
Sign up to set email alerts
|

ERp29, a general endoplasmic reticulum marker, is highly expressed throughout the brain

Abstract: ERp29 is a recently discovered resident of the endoplasmic reticulum (ER) that is abundant in brain and most other mammalian tissues. Investigations of nonneural secretory tissues have implicated ERp29 in a major role producing export proteins, but a molecular activity remains wanting for this functional orphan. Intriguingly, ERp29 appears to be heavily utilized in the cerebellum, a brain region not conventionally regarded as neurosecretory. To elucidate this functional quandary, we used immunochemical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 96 publications
4
32
0
Order By: Relevance
“…Mature ERp29 (25.6 kDa, MrZ29 000 on SDS-PAGE) has an N-terminal domain homologous to the thioredoxin-like domains in protein disulfide isomerase (PDI), and a C-terminal domain with similarities to the P5 subfamily of PDI , Liepinsh et al 2001, Sargsyan et al 2002a, 2002b, Mkrtchian & Sandalova 2006; a KDEL-variant motif at the C-terminus specifies retention in the ER. ERp29 is expressed ubiquitously in mammalian tissues, and homologous proteins have been identified in organisms as primitive as the fruit fly (Shnyder & Hubbard 2002, MacLeod et al 2004, Park et al 2005. These proteins are regarded to be specifically associated with the ER, mitochondria, Golgi, nuclei, or cell membrane (Huang et al 2002).…”
Section: Identification Of Erp29 In Epididymismentioning
confidence: 99%
See 4 more Smart Citations
“…Mature ERp29 (25.6 kDa, MrZ29 000 on SDS-PAGE) has an N-terminal domain homologous to the thioredoxin-like domains in protein disulfide isomerase (PDI), and a C-terminal domain with similarities to the P5 subfamily of PDI , Liepinsh et al 2001, Sargsyan et al 2002a, 2002b, Mkrtchian & Sandalova 2006; a KDEL-variant motif at the C-terminus specifies retention in the ER. ERp29 is expressed ubiquitously in mammalian tissues, and homologous proteins have been identified in organisms as primitive as the fruit fly (Shnyder & Hubbard 2002, MacLeod et al 2004, Park et al 2005. These proteins are regarded to be specifically associated with the ER, mitochondria, Golgi, nuclei, or cell membrane (Huang et al 2002).…”
Section: Identification Of Erp29 In Epididymismentioning
confidence: 99%
“…In humans, ERp29 is encoded by a single gene on chromosome 12 that has been highly conserved during mammalian evolution , Mkrtchian & Sandalova 2006. As ERp29 lacks the double cysteine motif, essential for PDI redox activity, it has been suggested that it plays a role in protein maturation and/or secretion, related to the chaperone function of PDI (Liepinsh et al 2001, Mkrtchian & Sandalova 2006, primarily in the production of endomembrane and secretory proteins (Shnyder & Hubbard 2002, MacLeod et al 2004. ERp29 is considered to be another major reticuloplasmin, thus adding distinct functionality to the ER machinery , MacLeod et al 2004, Hermann et al 2005.…”
Section: Identification Of Erp29 In Epididymismentioning
confidence: 99%
See 3 more Smart Citations